Helping students to cope with their communication apprehension / Francis Xavier A.S. Rajoo and Wan Zulkipli Wan Salleh - A.S. Rajoo, Francis Xavier; Wan Salleh, Wan Zulkipli (Universiti Teknologi MARA, Kedah, 2013)
One of the fundamental skills required of students when they are in transition to the professional world is proficiency in English language communication. However, many students have yet to reach a reasonable level of competence in their communicative skills. It is not surprising to find students who still find it difficult to express themselves fluently even at tertiary level. Their weaknesses are often coupled with feelings of fear and anxiety that intensify when these students are engaged in conversations with people from different cultures. Such fear and anxiety is termed communication apprehension and it can be measured. One way to help students to cope with their shortcomings is to encourage them to make selfassessments of their communication apprehension. In this limited study, a self-report inventory, the 'Personal Report of Intercultural Communication Apprehension' questionnaire was administered to selected undergraduate students at a private institution of higher learning in order to identify their communication apprehension level. The data collected was analyzed using descriptive statistics. Factor analysis was used to determine the dominant comment(s) pertaining to communication with respect to communication apprehension level, namely low, moderate and high. This self-report inventory could act as a useful guide for the students to develop coping mechanisms to overcome their fear and anxiety.